Lip balm made from butter extracted from bacuri (Platonia insignis Mart.) Amazonian fruit seeds: Development and characterization (Revista Brasileira de Plantas Medicinais, 2024)
With the growing demand in the cosmetic industry for plant-based ingredients, this article presents a novel approach to developing a lip balm from butter extracted from bacuri seeds (Platonia insignis Mart.). The physical-chemical characterization of the bacuri seed butter was conducted, including determining the melting point and fatty acid (AG) content by gas chromatography coupled with mass spectrometry (GC-MS). The lip balm formulation, obtained using the phase inversion method, was evaluated for its applicability through a rheological study. The melting point values found were 35 and 79 ºC for the formulation, aligning with values described in the literature. The AG composition of the butter sample revealed significant levels of palmitic acid (42,2%), oleic (28,8%), and palmitoleic (10,8%). In the rheological study, the lip balm exhibited the physical characteristics of a non-Newtonian fluid of the pseudoplastic thixotropic type, an ideal behavior for topical formulations. These results underscore the potential of the butter extracted from bacuri seeds as a promising alternative input for a unique and innovative lip balm product, instilling a sense of optimism in the reader.